Materials, energy and CNGDI vehicle engineering - Sahari, Barkawi (Universiti Putra Malaysia Press, 2009)

(untitled)
Materials, energy and car are essential for our daily life, especially, in our modern society. The common materials in mechanical engineering works are metal and composites. They are used in components for power generation, automotive vehicles and machineries. Some examples are vehicle body platforms, pressure vessels, engine cylinders, plates, heat exchangers, steam and gas turbines rotors, shafts and casing and gears. The common energy sources available are petroleum and natural gas. Other sources and forms are also available. Energy is needed for our daily activities. Cars are required to move us around. Materials, energy and cars are interrelated. Cars use materials in their construction and require energy to make them move. In the design of cars, materials and energy need to be considered. The lecture described the research tool (finite element) and its application to continuum mechanics of materials, followed by description on the behaviour, ratchetting of mechanical components and studies on crash behaviours. This is followed by description and discussion on the energy scenario for the years 2005 to 2050. The material research and energy studies have lead towards the development of Compressed Natural Gas Direct Injection (CNGDI) vehicle. A detail description on the development of CNGDI vehicle body platforms is given together with the crashworthiness characteristics results. The last section of the lecture describes how to manage a multi-institutional research project with specific reference to CNGDI Engine and Transmission under the IRPA PR mechanism from 2002 – 2007, led by UPM. The projects are multi-institutional research projects where, the author is the Program Head as well as Project Head for Vehicle Architecture and Integration.